2018
DOI: 10.1002/pola.29275
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of PLGA block molecular weight on gelling temperature of PLGA‐PEG‐PLGA thermoresponsive copolymers

Abstract: Thermoresponsive, biodegradable polymeric hydrogel networks are used widely in medicinal applications. Poly(d,l‐lactic acid‐co‐glycolic acid)‐b‐poly(ethylene glycol)‐b‐poly(d,l‐lactic acid‐co‐glycolic acid) (PLGA‐PEG‐PLGA) triblock copolymers exhibit a sol–gel transition upon heating. The effect of PLGA block and PEG chain molecular weights (MWs) on the gelling temperature of polymer aqueous solution (20% w/w) is described. All polymer solutions convert into a hard gel within 2 °C of the gelling temperature. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 23 publications
5
35
0
Order By: Relevance
“…The stretching frequency of CO is in 1748 and 1752 cm −1 ; 1107, 1088, and 1113 cm −1 are stretching vibration of C–O and C–O–C. The IR ester band at 1750 and 1100 cm −1 indicates ester bond formation (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…The stretching frequency of CO is in 1748 and 1752 cm −1 ; 1107, 1088, and 1113 cm −1 are stretching vibration of C–O and C–O–C. The IR ester band at 1750 and 1100 cm −1 indicates ester bond formation (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…If the gel did not flow, the temperature was recorded as the gelling temperature of the solution (T gel ). Results are accurate to +/−2.0 °C [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, several drawbacks to the applicability of PCL–PEG–PCL triblock copolymers remain, and a study of the effect of high molecular weight has, to the best of our knowledge, yet to be reported. High molecular weight polymers may reduce the gelation temperature required to form the hydrogel, thus allowing the possibility of injection as a liquid and subsequent formation of a hydrogel post-injection, as is commonly employed with the triblock copolymer analogue with PLGA [ 15 ]. Furthermore, the crystallinity of PCL does not allow for a stable aqueous solution, and the relatively short PCL blocks render a short shelf-life of the polymer [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gel-to-sol or sol-to-gel transition only with appropriate Mw and MWD [21] Wider Mw/Mn of PEG block sometimes led to the coexistence of sol-to-gel transition upon cooling and upon heating PLGA/PEG ratio Linear relation between T gel and PLGA/PEG ratio [22] PEG molecular weight T gel dependency on PLGA/PEG ratio became less obvious as PEG molecular weight increased [22] Positional isomer of coupling agent o-PC had smaller coil size compared to m-PC and p-PC [23] o-PC exhibited lower T gel and higher modulus compared to m-PC and p-PC MWD, molecular weight distribution; Mw, weight-average molecular weight; Mn, number-average molecular weight; CMC, critical micelle concentration; CGC, critical gel concentration; PEG, polyethylene glycol; PLGA, poly(lactic acid-co-glycolic acid); PC, phthaloyl dichloride.…”
Section: Mwd Of Peg Blockmentioning
confidence: 99%
“…Recently, Steinman et al first reported the effect of the PLGA/PEG ratio and PEG molecular weight on T gel of PLGA-PEG-PLGA aqueous solution (20 wtr%). They revealed a linear relation between T gel and the PLGA/PEG ratio and variation in Tgel dependence on the PLGA/PEG ratio based on PEG molecular weight [22].…”
Section: Mwd Of Peg Blockmentioning
confidence: 99%